Global e-government theory, applications and benchmarking - Al-Hakim, Latif 1946-.; Gale Group (Hershey, Penn. Idea Group Pub., 2007)
This handbook provides helpful examples from practitioners and managers involving real-life applications, while academics and researchers in the fields of information systems and e-government contribute theoretical insights.
"Interest in e-government, both in industry and in academies, has grown rapidly over the past decade. This book provides helpful examples from practitioners and managers involving real-life applications; academics and researchers contribute theoretical insights"--Provided by publisher.
Electronic reproduction.
Keywords: Internet in public administration; Electronic books